Effect of life skills education on nurses’ happiness - Fateme Rahighee Yazdi; Farahnaz Farnia; Maryam Salehzadeh Abarghouei (American Journal of Experimental and Clinical Research, 2016)
Happiness is known as a common goal for all the human being and an effective factor in reducing and coping with stress. Nursing is one of the stressful jobs in healthcare facing various occupational stressors. Life skills education is an intervention used to promote mental health and confront psychosocial injuries. The present study was conducted to examine the effect of life skills education on nurses’ happiness at Shahid Sadoughi Hospital in Yazd, 2015. This is a semi-experimental study with pre- and post-test and a control group. A total of 32 volunteer nurses were selected and assigned into control (n=16) and case (n=16) groups. The case group participated in an 8-hour course of life skills education (including effective communication, self-awareness, anger management, and coping with stress). Data collection was carried out using Fordyce happiness scale and demographic questions completed before and one week after the course by both groups and analyzed using chi square and t-test. According to the findings of this study the mean (±SD) of nurses’ happiness in the control and case groups were 131.25 ± 11.96 and 130.44 ± 12.75 at the baseline and 130.06 ± 28.10 and 146.25 ± 13.70 one week later, respectively (P = 0.038). This difference was not significant in control group (P = 0.163). The results of this study indicated that life skills education could significantly increase nurses’ happiness and thus it can be used as a beneficial intervention.